Phenylethylpyranone and aristolochic acid derivatives from Aristolochia urupaensis - Holzbach, Juliana C. [UNESP]; Nascimento, Isabele R. [UNESP]; Lopes, Lucia M. X. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2017)
A new pyranone, (S)-2-(4-hydroxyphenylethyl)-6-methyl-2,3-dihydro-4H-pyran-4-one, with unusual carbon skeleton, and three new aristolochic acid derivatives (7-O-methylaristolochic acid F, sodium 7-O-methylaristolochate F and sodium aristolochate F) were isolated from Aristolochia urupaensis (Aristolochiaceae) stems together with 31 known compounds. The structures of the compounds were determined by spectroscopic analyses, including Fourier transform infrared (FTIR) and 1D and 2D nuclear magnetic resonance (NMR) techniques, and high-resolution mass spectrometry (HRMS).
Keywords: Aristolochia urupaensis; Aristolochiaceae; Phenylethylpyranone; Sodium aristolochate